THE ADJECTIVE LIBER AND ITS’ DERIVATIVES IN PLAUTUS’ WORD PLAYS (Annual of the Faculty of Philosophy in Skopje, 2016)
The adjective liber, „free, released, loose, unoccupied“ from the Indoeuropean root *Hjleudh-, „grow“ and its derivatives libertas, „freedom“, libertus and libertinus, „freedman“, lib ero, „free“, liberälis, „free, noble, generous“, lîberï, „children“, Liber, „Liber, Liberator“ play significant role in creating wordplays in the works of the Roman comediographer Plautus. The analysis of the examples shows that these words on one hand were used by Plautus for creation offunny situations of misunderstanding, based on their polysemy. On the other hand Plautus puts them in a context with other words, that are not etymologically related, by sound similarly. This second type of wordplays is important testimony for the semantical development of the adjective liber and its derivatives in Old Latin, but also for an additional analysis of the understanding of the term „freedom “ by Latins.
Keywords: LIBER; PLAUTUS; WORDPLAY